THE IMPORTANCE OF TEACHING RELIGIOUS MODERATION IN SHAPING PLURALIST UNDERSTANDING IN ISLAMIC EDUCATION - Angranti, Wiwik (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Background: Islamic education plays a significant role in shaping the identity and values of Muslims. However, the challenges of globalization and diversity require a more inclusive and moderate teaching approach to promote social harmony. Research Objectives: This study aims to analyze the importance of teaching religious moderation in Islamic education and identify effective strategies for integrating moderation values into the Islamic education curriculum. Method: The method used in this research is qualitative with a literature study approach. Data were obtained from various relevant literature, including books, journals, articles, and other academic sources discussing religious moderation and Islamic education. The data were thematically analyzed to identify key concepts and strategies for integrating moderation values in Islamic education. Results: The research results show that teaching religious moderation can strengthen students' understanding of diversity and the importance of tolerance. A moderate approach in Islamic education helps create an inclusive learning environment that respects differences and encourages constructive intercultural dialogue. Several concrete strategies for integrating moderation values include curriculum revision, teacher training, and organizing interfaith dialogue programs. Conclusion: The implementation of moderation values in Islamic education can help reduce interfaith conflicts and promote social harmony. Moderate education plays an important role in shaping a more tolerant and inclusive generation. Therefore, educational policies that support the teaching of religious moderation and training for teachers to facilitate inclusive learning are needed.